2016
DOI: 10.1007/s00210-016-1234-6
|View full text |Cite
|
Sign up to set email alerts
|

Tempol and perindopril protect against lipopolysaccharide-induced cognition impairment and amyloidogenesis by modulating brain-derived neurotropic factor, neuroinflammation and oxido-nitrosative stress

Abstract: We aim to evaluate the protective role of the central angiotensin-converting enzyme (ACE) inhibitor perindopril, compared with the standard reactive oxygen species (ROS) scavenger tempol, against lipopolysaccharide (LPS)-induced cognition impairment and amyloidogenesis in a simulation to Alzheimer's disease (AD). Mice were allocated into a control group, an LPS control group (0.8 mg/kg, i.p., once), a tempol (100 mg/kg/day, p.o., 7 days) treatment group, and two perindopril (0.5 and 1 mg/kg/day, p.o., 7 days) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 123 publications
1
30
0
1
Order By: Relevance
“…Tempol treatment significantly increased brain antioxidant capacity in the older rats, whereas a slight, nonsignificant increase was observed in SOD. Other researchers have shown that tempol treatment was effective in increasing SOD activity and GSH activity in young brains (Ali et al 2016). However, our findings did not confirm any increase in antioxidant enzymes in either the brain or the hypothalamus.…”
Section: Discussionmentioning
confidence: 94%
“…Tempol treatment significantly increased brain antioxidant capacity in the older rats, whereas a slight, nonsignificant increase was observed in SOD. Other researchers have shown that tempol treatment was effective in increasing SOD activity and GSH activity in young brains (Ali et al 2016). However, our findings did not confirm any increase in antioxidant enzymes in either the brain or the hypothalamus.…”
Section: Discussionmentioning
confidence: 94%
“…Lipopolysaccharide (LPS) as a potent bacterial endotoxin, triggers production of inflammatory cytokines such as TNF-α induces ROS production [5]. On the other hand, LPS was recently reported to be able to cause amyloidogenesis in the hippocampal formation and has been used to induce an animal model of AD when it was administered to normal and transgenic rodents [6]. It has also been well documented Aβ induced LTP impairment is mediated by activation of iNOS [7].…”
Section: Introductionmentioning
confidence: 98%
“… 2016 ) and neurodegeneration (Ali et al. 2016b ). We may conclude that Quillaja saponaria bark saponin is a promising hepatoprotective agent acting, at least partly, through scavenging free radicals and downregulation of nitric oxide production.…”
Section: Discussionmentioning
confidence: 99%